2015
DOI: 10.1007/s11060-015-2003-y
|View full text |Cite
|
Sign up to set email alerts
|

XBP1 silencing decreases glioma cell viability and glycolysis possibly by inhibiting HK2 expression

Abstract: Glioma cells rely on glycolysis to obtain energy and sustain their survival under microenvironmental stress in vivo. The mechanisms of regulation of glycolysis in glioma cells are unclear. Signaling pathway mediated by the transcription factor X box-binding protein 1 (XBP1) is one of the most important pathways of unfolded protein response which is comprehensively activated in cancer cells upon the microenvironmental stress. Here we showed that XBP1 was significantly activated in glioma tissues in vivo. XBP1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Specifically, our data imply a more prominent role for XBP1 in the regulation and process of glycolysis. This finding is in line with a recent report demonstrating that silencing XBP1 in glioma cells inhibits glycolysis resulting in reduced ATP production and decreased cancer cell survival [ 26 ]. Long-term activation of the IRE1 signaling has also been shown to reduce glucose metabolism and mitochondrial function; however, it is unclear whether this effect is mediated by XBP1 [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, our data imply a more prominent role for XBP1 in the regulation and process of glycolysis. This finding is in line with a recent report demonstrating that silencing XBP1 in glioma cells inhibits glycolysis resulting in reduced ATP production and decreased cancer cell survival [ 26 ]. Long-term activation of the IRE1 signaling has also been shown to reduce glucose metabolism and mitochondrial function; however, it is unclear whether this effect is mediated by XBP1 [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, splicing and activation of XBP1 and its complex formation with HIF-1α was recently shown to enhance a hypoxic phenotype and subsequently promote the progression of triple negative breast cancers 45 . The XBP1/HIF-1α complex binds to and regulates genes associated with the Warburg phenotype 45 , and XBP1 silencing abrogates the glycolytic phenotype of gliomas 89 . We have shown previously that adipocytes promote oxygen-independent HIF-1α activation in prostate cancer cells and that HIF-1α signaling is responsible for adipocyte-induced glycolytic phenotype 6 .…”
Section: Discussionmentioning
confidence: 99%
“…25 In contrast, XBP1 silenced glioma cells showed a decreased capacity of tumor formation. 29 Moreover, several studies demonstrated that the knock-down of XBP1 gene expression promotes impairment of tumor growth and tumor cell invasion. 24,30 Similarly, low expression of UPR including (XBP1) in PCa may permit cancer cells to escape apoptosis and support tumorgenesis.…”
Section: Discussionmentioning
confidence: 99%